2003
DOI: 10.1521/pedi.17.6.497.25354
|View full text |Cite
|
Sign up to set email alerts
|

Frontal Lobe Dysfunctions in Borderline Personality Disorder? Neuropsychological Findings

Abstract: This study aims to determine whether specific neuropsychological performance impairments in borderline patients can be objectified and whether these findings indicate frontal dysfunctions. Twenty-three patients with borderline personality disorder and 23 normal controls were examined using a neuropsychological test battery to assess intelligence, attentiveness, proneness to interference, learning and memory, as well as planning and problem solving. All subjects filled out standardized questionnaires to assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
61
2
4

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 29 publications
9
61
2
4
Order By: Relevance
“…Most self-report scales showed large group differences, with BPD subjects showing stronger impulsivity. Higher values for BPD patients on these scales are in line with many other studies using self-report measures in BPD [10][11][12][13][14][15]17] . High overall interrelations between different self-report scales indicate that, in general, they measure rather similar constructs.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Most self-report scales showed large group differences, with BPD subjects showing stronger impulsivity. Higher values for BPD patients on these scales are in line with many other studies using self-report measures in BPD [10][11][12][13][14][15]17] . High overall interrelations between different self-report scales indicate that, in general, they measure rather similar constructs.…”
Section: Discussionsupporting
confidence: 89%
“…While Leyton et al [18] found significantly more errors in a go/no go task in a group of 13 BPD patients, and Rentrop et al [19] found more commission errors in BPD patients as compared to HC, most studies have failed to find deficits in BPD samples. Two studies did not find a different performance in go/no go tasks in groups of 9 patients each [11,20] . Similarly, other studies did not find differences between 24 BPD patients as compared to patients with major depression (MDD) and to HC in a stop signal task, a continuous performance task and a card sorting test [21] , or did not report significant differences between BPD subjects and HC in a stop signal task [22] .…”
Section: Empirical Findings On Impulsivity In Bpdmentioning
confidence: 90%
See 1 more Smart Citation
“…In both studies no significant difference in response inhibition between the groups was found [15,16] . However, at least in 1 study the sample size of n = 8 might have resulted in insufficient power to detect differences.…”
Section: Introductionmentioning
confidence: 70%
“…So far, only visual Go/Nogo tasks have been used in BPD patients, but no indicators were found for impaired performance [15,16] .…”
Section: Discussionmentioning
confidence: 99%